Perceived Quality Drives Indonesian Purchase Intention for Fermented Drinks - Nurfaida, Avesta Angelia (APPS Publications, 2023)
Objective – This study aims to determine people's perceptions of fermented drinks through its value, and quality which then lead to Indonesian purchase intention on fermented drinks. Methodology – An online survey was used to gather information from respondents of various ages and professions who enjoy drinking fermented beverages as well as those who are unsure of what it is and its advantages. Fermented beverages are still not categorized as alcoholic beverages, but with some restrictions. A linear regression model was used in SPSS 3 version to examine the data gathered for this study. Findings – The outcome demonstrates that the significant hypothesis only applies to hypothesis 1, which states that perceptions of fermented drink quality simultaneously influence Indonesian buying intentions in a favorable way. Additionally, a significant positive connection is shown in this study between the dependent variable of purchase intention and the independent variable of perceived quality. Hypothesis 2, on the other hand, which holds that perceived value and Indonesian buy intention are strongly correlated, is not supported by the data and has a modest positive association. Novelty – While there might be studies on fermented drinks and consumer behavior, focusing specifically on the Indonesian context is a unique angle.